Evaluation of surgical management of primary spinal tumours - Chowdhury, AZ; Hossain, MT; Chowdhury, AI; Salek, KM; Kaiser, MS; Arifin, KN (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):594-600 The abstract of this article is available on the PubMed website